Peran Instagram @greenarationid sebagai Media Kampanye Ramah Lingkungan - Iqbal Yusra Karim; Neni Yulianita (Jurnal Riset Public Relations, 2021)
Abstract. Social media facilitates users to do activities or collaborate so that they connect with other users. This research The role of Instagram @greenerationid as an Environmentally Friendly Campaign Media aims to show the role of social media in campaigns that apply the management function or the role of PR in managing communication, which cannot separate from interactions with the public, both with internal publics and external publics of the company to get a good image and reputation. This research uses a case study approach and approach, examines and analyzes the communication and strategy of the media team in managing the @greenerationid Instagram account as an environmentally friendly media campaign. This research on the role of Instagram as an environmentally friendly campaign media shows that the programs created by GF campaigning for SCP issues communicate through Instagram. Have a series of planned communications to a broader audience and Cooperation partners to build a positive image. In the process, there are PR activities and PR in Instagram management through social media functions. Abstrak. Media sosial memfasilitasi pengguna untuk beraktivitas atau berkolabolarasi sehingga terhubung dengan pengguna lainnya. Dalam penelitian ini Peran Instagram @greenerationid sebagai Media Kampanye Ramah Lingkungan bertujuan memperlihatkan peran media sosial dalam kampanye yang mengaplikasikan fungsi manjemen atau peranan PR dalam pengelolaan komunikasi, dimana tidak terlepas dengan adanya interaksi dengan publik- publik, baik itu dengan publik internal maupun publik eksternal perusahaan sehingga mendapatkat citra dan reputasi yang baik. Penelitian ini menggunakan metode kualitatif dan pendekatan studi kasus, mengkaji dan menganalisis komunikasi dan strategi tim media dalam mengelola akun Instagram @greenerationid sebagai media kampanye ramah lingkungan. Penelitian mengenai Peran Instagram sebagai media kampanye ramah lingkungan ini memperlihatkan Program-Program yang diciptakan GF mengkampanyekan isu SCP dikomunikasikan melalui Instagram. Memiliki serangkaian komunikasi yang terencana kepada khalayak luas dan juga mitra kerjasama untuk menciptakan citra positif. Dalam prosesnya terdapat aktifitas dan PR dalam pengelolaan Instagram melalui fungsi media sosial.